Graph analysis and visualization : discovering business opportunity in linked data - Brath, Richard; Jonker, David (John Wiley & Sons, 2015)
Graph Analysis and Visualization brings graph theory out of the lab and into the real world. Using sophisticated methods and tools that span analysis functions, this guide shows you how to exploit graph and network analytic techniques to enable the discovery of new business insights and opportunities. Published in full color, the book describes the process of creating powerful visualizations using a rich and engaging set of examples from sports, finance, marketing, security, social media, and more. You will find practical guidance toward pattern identification and using various data sources, including Big Data, plus clear instruction on the use of software and programming. The companion website offers data sets, full code examples in Python, and links to all the tools covered in the book. Science has already reaped the benefit of network and graph theory, which has powered breakthroughs in physics, economics, genetics, and more. This book brings those proven techniques into the world of business, finance, strategy, and design, helping extract more information from data and better communicate the results to decision-makers.- Resumé vydavatel
Includes index.
Keywords: síťová analýza; teorie grafů; zpracování dat; podnikání; network analysis; graph theory; data processing; business; elektronické knihy; sborníky; electronic books; papers of several authors